PERAN GURU PAI DALAM MENGEMBANGKAN KREATIVITAS DAN INOVASI PADA SISWA DI SMP NEGERI 1 SANGATTA UTARA - Siti Nilam; Eko Nursalim (PT. Pustaka Andil Lestari, 2024)
Islamic Religious Education (PAI) plays a strategic role in fostering students' creativity and innovation to face the challenges of modern life while upholding Islamic values. This study aims to explore the role of PAI teachers in promoting the development of students' creativity and innovation, as well as identifying the challenges and solutions in the learning process at SMP Negeri 1 Sangatta Utara. This research employs a descriptive qualitative approach, utilizing data collection methods such as observation, interviews, and documentation, which are analyzed using an interactive model (data collection, data reduction, data presentation, and conclusion drawing). The findings indicate that PAI teachers play a central role as facilitators, motivators, and inspirers in learning activities that support students' creativity development. The use of technology-based learning methods, project-based approaches, and digital media helps students think critically and creatively. Teachers also create an interactive learning environment that allows students to explore, discuss, and collaborate. The school principal and PAI teachers emphasize the importance of teacher training and learning approaches aligned with contemporary developments to encourage students to learn actively and creatively.